Demystifying numerical models : step-by step modeling of engineering systems - Mo, John P. T.; Cheung, Chi Pok; Das, Raj (Elsevier Science & Technology, 2018)
Demystifying Numerical Models: Step-by Step Modeling of Engineering Systems is the perfect guide on the analytic concepts of engineering components and systems. In simplified terms, the book focuses on engineering characteristics and behaviors using numerical methods. Readers will learn how the computational aspects of engineering analysis can be applied to develop various engineering systems to a level that is fit for implementation.